Prognostic value of elective neck dissection in adenoid cystic carcinoma of head and neck: a meta-analysis: A call for randomized trials and international consensus. Issue 11 (November 2021) - Suton, P.; Luksic, I.
Abstract: Adenoid cystic carcinoma of head and neck (AdCCHN) is an uncommon salivary gland cancer characterized for infrequent neck metastases, and high rate of local and distant recurrence. The aim of this meta-analysis was to analyse the significance of elective neck dissection (END) in terms of overall survival (OS) in patients with AdCCHN. A systematic literature search and meta-analysis was performed. Endpoint assessed by this meta-analysis included 5-year OS (death from any cause). Statistical heterogeneity was assessed using the Cochrane Q test and I 2 statistic. A pooled odds ratio (OR) was reported with 95% confidence interval (CI). There were 1934 patients in the END arm and 3083 in the observation group. The pooled OR, calculated for END vs. observation, was 0.94. Patients receiving END had similar risk for death compared to observation cohort ( P = 0.76). No significant difference in final outcome after patient stratification based on T stage was identified (OR for T1/T2 1.27, P = 0.39; OR for T3/T4 0.95, P = 0.90). Observation for cN0 neck is a reasonable option in AdCCHN. These findings suggest the need for prospective trials on indications and extent of END in AdCCHN.